PERANAN MASYARAKAT DALAM PEMBANGUNAN INFRASTRUKTUR DI DESA TANA TORO KECAMATAN PITU RIASE KABUPATEN SIDENRENG RAPPANG - Yani, Ahmad; Hamid, Hriyanti; Asad, Muh. Arisal (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The aim of the research is to determine the role of the community in infrastructure development in Tana Toro Village, Pitu Riase District, Sidenreng Rappang Regency, and to find out the factors that influence what factors influence the community's role in infrastructure development in Tana Toro Village, Pitu Riase District, Sidenreng Rappang Regency. . This research method approach uses a quantitative descriptive approach. The population in this study was 579 people with 85 samples. The sampling technique used is a saturated sample (census). The data collection techniques used in this research are observation, interviews, questionnaires and literature study. The data collected was then processed and analyzed using quantitative descriptive analysis techniques with the help of descriptive statistics using SPSS and percentages. The results of the research show that the recapitulation of infrastructure development in Tana Toro Village, Pitu Riase District, Sidenreng Rappang Regency with a percentage result of 70% in the good category, as well as the factors that influence infrastructure development in Tana Toro Village, Pitu Riase District, Sidenreng Rappang Regency with a percentage recapitulation result of 60 % in the good category.